The Effectiveness of Fundraising Strategies at BAZNAS Bulukumba - Syamsidar Nur; Hasyim Hasyim; Andi Haerani (Contemporary Journal on Business and Accounting, 2026)
Purpose – This research investigates the effect of effectiveness on the fundraising strategies implemented by the national Zakat Amil agency of Bulukumba Regency during the 2020-2022 period. Design/methodology/approach – This research uses a mixed methods approach, which combines qualitative and quantitative methods in a single study. The data sources used in this research consist of two types, namely primary data obtained from interviews or questionnaire completion and secondary data, which are data obtained in a finished form and collected from existing documents. Findings – The research results indicate that the effectiveness of fundraising strategies at the National Amil Zakat Agency (BAZNAS) of Bulukumba Regency experienced a significant increase during the 2020–2022 period, as evidenced by the rise in the number of donors, the amount of funds received, and the enhancement of the institution's image in the eyes of the public. This increase is inseparable from the implementation of strategies based on SWOT analysis, which placed the organization in an aggressive position (growth-oriented strategy), enabling it to optimally utilize internal strengths and external opportunities. Originality – The findings of the research also indicate that the effectiveness of fundraising strategies is not only measured by the amount of funds raised, but also by the institution's ability to build long-term relationships with donors, increase public trust, and maintain program sustainability. This aligns with the view that effective fundraising must be able to integrate financial and non-financial aspects in its management.